E-READINESS DALAM PENERAPAN IDENTITAS KEPENDUDUKAN DIGITAL DI KABUPATEN KARAWANG - , Mira Amelia; Dadan Kurniansyah,; Dewi Noor Azijah, (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
The Population and Civil Registration Service of Karawang Regency has implemented and served the activation of the Digital Population Identity (IKD) application since the end of 2022. To minimize implementation failures, careful preparation is required beforehand, including determining the level of readiness for implementing Digital Population Identity. This research aims to analyze the readiness of the Karawang Regency Regional Government in implementing the Digital Population Identity application using Musa's e-readiness theory. The method in this research is a descriptive method with a qualitative approach. The results obtained from the research show that e-readiness in the implementation of Digital Population Identity in Karawang Regency has two perspectives, namely based on the government's perspective in the form of the availability of technology to support the IKD implementation mechanism, the understanding and skills possessed by employees regarding Digital Population Identity are good, already availability of legal instruments and programs regarding the implementation of Digital Population Identity activation services. Meanwhile, based on the community's perspective, it is considered to have several shortcomings caused by the community's understanding and participation in Digital Population Identity being considered to be still lacking.